Transient gestational hypothyroxinemia accelerates and enhances ulcerative colitis-like disorder in the male offspring - Rivera, Juan Carlos; Opazo, Ma. Cecilia; Hernández-Armengol, Rosario; Álvarez, Oscar; Mendoza-León, María José; Caamaño, Esteban; Gatica, Sebastian; Bohmwald, Karen; Bueno, Susan M.; González, Pablo A.; Neunlist, Michel; Boudin, Helene; et al. (Frontiers in Endocrinology, 2024)
Introduction Gestational hypothyroxinemia (HTX) is a condition that occurs frequently at the beginning of pregnancy, and it correlates with cognitive impairment, autism, and attentional deficit in the offspring. Evidence in animal models suggests that gestational HTX can increase the susceptibility of the offspring to develop strong inflammation in immune-mediated inflammatory diseases. Ulcerative colitis (UC) is a frequent inflammatory bowel disease with unknown causes. Therefore, the intensity of ulcerative colitis-like disorder (UCLD) and the cellular and molecular factors involved in proinflammatory or anti-inflammatory responses were analyzed in the offspring gestated in HTX (HTX-offspring) and compared with the offspring gestated in euthyroidism (Control-offspring). Methods Gestational HTX was induced by the administration of 2-mercapto-1-methylimidazole in drinking water to pregnant mice during E10–E14. The HTX-offspring were induced with UCLD by the acute administration of dextran sodium sulfate (DSS). The score of UCLD symptomatology was registered every day, and colon histopathology, immune cells, and molecular factors involved in the inflammatory or anti-inflammatory response were analyzed on day 6 of DSS treatment. Results The HTX-offspring displayed earlier UCLD pathological symptoms compared with the Control-offspring. After 6 days of DSS treatment, the HTX-offspring almost doubled the score of the Control-offspring. The histopathological analyses of the colon samples showed signs of inflammation at the distal and medial colon for both the HTX-offspring and Control-offspring. However, significantly more inflammatory features were detected in the proximal colon of the HTX-offspring induced with UCLD compared with the Control-offspring induced with UCLD. Significantly reduced mRNA contents encoding for protective molecules like glutamate-cysteine ligase catalytic subunit (GCLC) and mucin-2 (MUC-2) were found in the colon of the HTX-offspring as compared with the Control-offspring. Higher percentages of Th17 lymphocytes were detected in the colon tissues of the HTX-offspring induced or not with UCLD as compared with the Control-offspring. Discussion Gestational HTX accelerates the onset and increases the intensity of UCLD in the offspring. The low expression of MUC-2 and GCLC together with high levels of Th17 Lymphocytes in the colon tissue suggests that the HTX-offspring has molecular and cellular features that favor inflammation and tissue damage. These results are important evidence to be aware of the impact of gestational HTX as a risk factor for UCLD development in offspring.